Experimental study on strength and failure characteristics of mortar specimens with prefabricated cracks under uniaxial and triaxial stress - Pan, Xuwei; Wan, Li; Jiang, Tong; Jia, Yanchang; Zhang, Shuo (Frontiers in Materials, 2023)
Cracks in rock masses have adverse effects on their mechanical characteristics and the stability of rock mass engineering. For this experiment, uniaxial compression and true triaxial compression unloading tests were conducted on mortar specimens. The strength of the specimens was the lowest when the dip angle of the crack was 45°. Under uniaxial compression, the failure mode was mainly tensile failure. With an increase in the crack dip angle of the specimens, the types of cracks changed from shear to tensile cracks. Under true triaxial compression, the confining pressure considerably increased the strength and deformation characteristics of the specimens and weakened the influence of the crack dip angle on the strength. The failure mode when the crack dip angle was 15° was mainly tensile. The failure mode when the crack dip angles were 45° and 75° was mainly tensile–shear composite. With the increase in the crack dip angle, the failure degree of the specimens was more severe. Under the triaxial unloading confining, the failure mode was mainly shear. Compared with uniaxial compression, the failure degree of the specimens was more severe under true triaxial compression and true triaxial unloading. The innovation of this experiment is the use of a special mold to prepare specimens. We recommend that scholars conduct experimental and numerical simulation studies on different crack geometries.